2023
DOI: 10.1002/app.53733
|View full text |Cite
|
Sign up to set email alerts
|

P3HT and PEDOT:PSS printed thin films on chemiresistors: An economic and versatile tool for ammonia and humidity monitoring applications

Abstract: We hereby present the fabrication of simple and efficient humidity and ammonia sensors based on a chemiresistor design employing a differential measurement technique. Interdigitated electrodes are connected via PEDOT:PSS or P3HT polymers and a reproducible and scalable fabrication procedure is presented. This procedure utilizes pneumatic nozzle printing instead of drop or spin-based processes and includes an optimized encapsulation procedure and material for sealing the reference electrodes. The suitability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…[147] Based on remarkable progress on the hardware site within the last 10 years, e.g., the widespread use of smartphone apps or the possibility for large-scale data monitoring (10-100 km radius) using open access networks, which neither requires a phone or service contract [148], a strongly increasing demand for accurate and stable sensors can be expected. This could be solved by, e.g., Universal Serial Bus (USB, or USB C)-based sensing platforms, which can be easily coupled with the digital world [75]. Simple sensing concepts, such as, e.g., chemiresistors in combination with cMIPs, therefore bear a huge potential to be tailored for a wide range of practical applications based on their sensing layer.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[147] Based on remarkable progress on the hardware site within the last 10 years, e.g., the widespread use of smartphone apps or the possibility for large-scale data monitoring (10-100 km radius) using open access networks, which neither requires a phone or service contract [148], a strongly increasing demand for accurate and stable sensors can be expected. This could be solved by, e.g., Universal Serial Bus (USB, or USB C)-based sensing platforms, which can be easily coupled with the digital world [75]. Simple sensing concepts, such as, e.g., chemiresistors in combination with cMIPs, therefore bear a huge potential to be tailored for a wide range of practical applications based on their sensing layer.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Another challenge faced by PEDOT-based sensing layers in particular is the polymers' high hygroscopicity. Swelling and collapsing upon fluctuations in ambient humidity result in significant alterations of the polymers' electric conductivity unrelated to specific analyte interactions [75]. In order to reduce such humidity-induced changes, hydrophobic additives can be included in the imprinting protocol [76].…”
Section: Monomermentioning
confidence: 99%
“…Additionally, during the 1 h of recovery, an increase in resistance was observed, resulting in an upwards drift of the sensor. Kumpf et al found similar values for their P3HT-based sensor and further reported that low concentrations of P3HT (<5 mg/ml in toluene) have the tendency to reach cut-off value of 50 M overtime, resulting in a loss of conducting ability [21]. At low concentrations of ammonia (5 ppm), a fluctuation in resistance (noise) made it difficult to accurately calculate the control P3HT sensor performance.…”
Section: A Sensor Performancementioning
confidence: 90%